URGENSI PENELITIAN TINDAKAN KELAS DALAM KONTEKS PENINGKATAN PROFESIONALITAS GURU PENJAS - Dimyati Dimyati (Jurnal Pendidikan Jasmani Indonesia, 2009)
In order not to make classroom action research (CAR) out of its core, at least there are five things that must be known and understood by a physical educator before designing and implementing classroom action research, which are: (1) CAR is a tool to improve or enhance the quality of teaching and educational implementation, therefore, appropriate learning methods and models should be chosen practically in order not to interfere or impede the commitment of daily duties; (2) the data collection techniques should not spend much time, so the main responsibility of physical educator/teacher is not neglected; (3) the research methodology should gives an opportunity for physical educator to formulate strong action reasearch hypothesis and determine appropriate strategies that suitable with the atmosphere and condition of the class; (4) The issues which raised should be updated and based on the responsibility of the area itself and also the problems which can be solved through CAR by physical educator itself; (5) CAR develop to the scopes of school. In this case, hopefully, all of school staffs give their participate and contribute, so that the other physical educator can feel the importance of that research. CAR will allows and facilitates physical educator to improve four competencies, those are: professionalism, pedagogical, personality, and social. The Understanding dan aplication of the CAR will help physical educator to developes four competencies requiered by the UU RI number 14 of 2005. Keywords : Classroom Action Research, Professionalism, Physical educator